Moderate molecular recognitions on ZnO m-plane and their selective capture/release of bio-related phosphoric acids. Issue 6 (2nd March 2022) - Kanao, Eisuke; Nakano, Katsuya; Kamei, Ryoma; Hosomi, Takuro; Ishihama, Yasushi; Adachi, Jun; Kubo, Takuya; Otsuka, Koji; Yanagida, Takeshi
Abstract : We reported molecular recognition on ZnO nanowires grown in a capillary via liquid chromatography and demonstrated the separation of nucleotides. Abstract : Herein, we explore the hidden molecular recognition abilities of ZnO nanowires uniformly grown on the inner surface of an open tubular fused silica capillary via liquid chromatography. Chromatographic evaluation revealed that ZnO nanowires showed a stronger intermolecular interaction with phenylphosphoric acid than any other monosubstituted benzene. Furthermore, ZnO nanowires specifically recognized the phosphate groups present in nucleotides even in the aqueous mobile phase, and the intermolecular interaction increased with the number of phosphate groups. This discrimination of phosphate groups in nucleotides was unique to the rich (101̄0) m -plane of ZnO nanowires with a moderate hydrophilicity and negative charge. The discrimination could be evidenced by the changes in the infrared bands of the phosphate groups on nucleotides on ZnO nanowires. Finally, as an application of the molecular recognition, nucleotides were separated by the number of phosphate groups, utilizing optimized gradient elution on ZnO nanowire column. Thus, the present results elucidate the unique and versatile molecular selectivity of well-known ZnO nanostructures for the capture and separation of biomolecules.